Energy Security and Geopolitics: The Case of the Russia–Ukraine Conflict - Mohaimen Nawab (`, 2025)
The Russia–Ukraine conflict, escalating from Crimea’s 2014 annexation to the 2022 full-scale invasion, has fundamentally reshaped global energy security and geopolitical dynamics. This study examines energy as a weapon of statecraft, tracing the collapse of Europe’s Russian gas dependency from 155 billion cubic meters (bcm) in 2021 to under 35 bcm projected for 2025. Through a qualitative embedded case study integrating secondary data from Eurostat, IEA reports, and Gazprom disclosures, alongside content analysis of policy documents and real-time X/Twitter sentiment, the research maps pipeline disruptions (e.g., Nord Stream sabotage, Yamal-Europe halt), market pivots (Russia’s Power of Siberia ramp-up to 38 bcm annually to China), and Europe’s REPowerEU-driven diversification (U.S. LNG surging 140%, renewables reaching 42.5% electricity share in Q1 2025). Findings reveal energy weaponization evidenced by 2021–2022 withholdings and Ukraine’s transit atrophy from 90 bcm pre-2019 to 15 bcm in 2024 while sanctions curtailed Russian revenues by over $300 billion despite shadow fleet evasion. Theoretically, the crisis validates offensive realism’s resource-power nexus while debunking liberal interdependence, as coercion trumped mutual restraint. Broader impacts include accelerated green transitions in Europe juxtaposed with short-term coal revival and global food insecurity via 80% fertilizer price spikes. Policy implications stress strategic reserves, supplier diversification, and multilateral governance to safeguard infrastructure and equity. The conflict heralds a multipolar energy order, where resilience demands not only technological adaptation but geopolitical foresight to prevent energy from remaining a vector of instability. Keywords: Energy Security, Geopolitics, Russia–Ukraine Conflict, Natural Gas Pipelines, Sanctions, LNG Diversification, Energy Weaponization, Renewable Transition, Multipolarity